Characteristics associated with media use in early adolescence - José Godinho; Joana Araújo; Henrique Barros; Elisabete Ramos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This study aimed to identify socioeconomic and behavioral characteristics associated with media use in early adolescence. The sample was comprised of 1,680 adolescents (884 girls and 796 boys) aged 13, attending private and public schools in Porto, Portugal, during 2003/2004. Adolescents completed questionnaires pertaining to demographic, social and behavioral characteristics, including the time spent watching television and playing computer games on week and weekend days. Logistic and proportional ordinal regressions showed that attending public schools, sleeping less time, using tobacco and presenting low levels of physical activity were factors associated with high media use. In boys living with one of their parents as well as living with younger and older parents were also associated with high media use. Besides the association with less healthier behaviours, we also found higher media use among adolescents from lower social classes and less structured families, which may increase their exposure to negative influence of the media.